2021
DOI: 10.1111/ijcp.14107
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug‐drug interactions with psychotropic drugs in paediatric inpatients: A cross‐sectional study

Abstract: Aims Polypharmacy and drug‐drug interactions (DDIs) are important problems that necessitate more attention in paediatric inpatients. This study aimed to determine and evaluate DDIs in paediatric inpatients using psychotropic drugs. Methods It was conducted as a retrospective cross‐sectional study. Inpatients consulted by child and adolescent psychiatrists (CAPs) and had at least one psychotropic drug‐using between January 2016 and September 2017 were retrospectively included. To determine the clinical signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
0
1
Order By: Relevance
“…Interestingly, the only admission without psychotropic DDI was a patient admitted for drug dependence rehabilitation and prescribed for vitamin supplements and supportive therapies. Our findings confirmed the high prevalence of psychotropic DDIs detected by electronic databases in the psychiatric inpatient settings [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the only admission without psychotropic DDI was a patient admitted for drug dependence rehabilitation and prescribed for vitamin supplements and supportive therapies. Our findings confirmed the high prevalence of psychotropic DDIs detected by electronic databases in the psychiatric inpatient settings [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…confirmed the high prevalence of psychotropic DDIs detected by electronic databases in the psychiatric inpatient settings [21,22]. However, the median of number of medications prescribed during hospitalisation was 9 and this limited its generalisability with patients in the psychiatric outpatient department, where the number of medications prescribed was comparatively lower [23].…”
Section: Plos Onementioning
confidence: 78%
“…29 Moreover, this study showed that the actual rate of drug-drug interactions was 20.6%. This rate was lower than some other studies in Turkey (76.5%) 30 or USA (49%). 31 This result suggested that drug-drug interactions in our sample could still be under control.…”
Section: Discussioncontrasting
confidence: 73%